School Principals’ Work Intensification and Resilience: A Call for Structural Change - Pollock, Katina; Nielsen, Ruth; Singh, Shankar (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2023)
Throughout the COVID-19 pandemic, principals have taken on increased responsibilities. Principals who are thriving are praised for their resilience while those who are struggling are inundated with calls to build their resilience. In this conceptual article, we problematize the overemphasis on individual responsibility that is implicit in pro-resilience narratives. We reviewed the interdisciplinary literature and used an inductive approach to examine resilience narratives across historical and disciplinary arcs, with specific attention given to the school leadership literature. We argue that, within the context of this pro-resilience movement, if attention is not given to the structural conditions of work intensification, the education system is setting K–12 principals up to experience adverse unintended consequences. These consequences can worsen existing mental health issues, such as occupational burnout, or exacerbate mental health stigma. We conclude by suggesting that structural changes could disrupt this individualization of responsibility and overreliance on the personal resiliency of school principals.